From Isocyanides to Iminonitriles via Silver-mediated Sequential Insertion of C(sp(3))–H Bond - Chi, Huiwen (iScience, 2019)
Heterocycles are prevalent constituents of many marketing drugs and biologically active molecules to meet modern medical challenges. Isocyanide insertion into C(sp(3))–H bonds is challenging especially for the construction of quaternary carbon centers. Herein, we describe an efficient strategy for the synthesis of α-iminonitrile substituted isochromans and tetrahydroisoquinolines (THIQs) with quaternary carbon centers through silver-triflate-mediated sequential isocyanide insertion of C(sp(3))–H bonds, where isocyanide acts as the crucial “CN” and “imine” sources. The produced α-iminonitriles have extensive applications as valuable synthetic building blocks for pharmacologically interesting heterocycles. This protocol could be further applied for the synthesis of iminonitrile-decorated phenanthridines and azapyrene. Interestingly, a remarkable aggregation-induced emission (AIE) effect was first observed for an iminonitrile-decorated pyrene derivative, which may open a particular area for iminonitrile applications in materials science.